PENGARUH PEMASARAN ONLINE TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS PADA KONSUMEN TOKO ACCESS COMPUTER SHOP - Krisa Krisa; Nuraini Asriati; Endang Purwaningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The aims of this study were: To find out the effect of online marketing on purchasing decisions for Asus laptops at consumers at Access Computer Shop shops. This study uses a quantitative research method with a causal approach. The population is consumers of Access Computer Shop stores with a sample size of 55 consumers and the data collection method uses a questionnaire which is distributed to consumers of Access Computer Shop stores via the Google form. The results showed: (1) Online marketing of Asus laptops to consumers at Acess Computer Shop stores was categorized as high with a percentage of 80.6%, (2) the purchasing decision rate for Asus laptops for consumers at Access Computer Shop stores was categorized as very high with a percentage of 82.34%. (3) There is a causal correlation of online marketing to the purchasing decision of Asus laptops for consumers at Access Computer Shop stores with a simple linear regression equation Y =40.719+ 0.915 X. The causal correlation of online marketing to purchasing decisions for Asus laptops for consumers at Access Computer Shop shops is evident from t test results with t count 3.465> t table 2.241 which means rejecting Ho and accepting Ha. The coefficient of determination of 0.321 indicates that online marketing has an effect of 23.1% on the decision to buy an Asus laptop and the remaining 76.9% is influenced by other variables.